Screening strategies to identify HSP70 modulators to treat Alzheimer’s disease - Repalli J; Meruelo D (Dove Medical Press, 2015)
Jayanthi Repalli, Daniel MerueloDepartment of Pathology, New York University, Langone Medical Center, New York, NY, USAAbstract: Alzheimer’s disease, the most common type of dementia, is a progressive brain disease that destroys cognitive function and eventually leads to death. In patients with Alzheimer’s disease, beta amyloids and tau proteins form plaques/oligomers and oligomers/tangles that affect the ability of neurons to function properly. Heat shock protein 70 (HSP70) has the ability to prevent aggregation/oligomerization of beta amyloid/tau proteins, making it a potential drug target. To determine this potential, it is essential that we have appropriate in vitro and cell-based assays that help identify specific molecules that affect this aggregation or oligomerization through HSP70. Potential drug candidates could be identified through a series of assays, starting with ATPase assays, followed by aggregation assays with enzymes/proteins and cell-based systems. ATPase assays are effective in identification of ATPase modulators but do not determine the effect of the molecule on beta amyloid and tau proteins. Molecules identified through ATPase assays are validated by thioflavin T aggregation assays in the presence of HSP70. These assays help uncover if a molecule affects beta amyloid and tau through HSP70, but are limited by their in vitro nature. Potential drug candidates are further validated through cell-based assays using mammalian, yeast, or bacterial cultures. However, while these assays are able to determine the effect of a specific molecule on beta amyloid and tau, they fail to determine whether the action is HSP70-dependent. The creation of a novel, direct assay that can demonstrate the antiaggregation effect of a molecule as well as its action through HSP70 would reduce the number of false-positive drug candidates and be more cost-effective and time-effective.Keywords: heat shock protein 70, beta amyloid, tau, adenosine triphosphatase activity, oligomers, aggregation